PENGARUH JUMLAH KUNJUNGAN WISATAWAN, TINGKAT HUNIAN HOTEL, LAMA MENGINAP WISATAWAN TERHADAP PERTUMBUHAN EKONOMI KALIMANTAN SELATAN - RAFLI SAFRIANNUR FADHILA (PPJP Universitas Lambung Mangkurat, 2019)
The researchis testing whether the magnitude is significant simultaneously and the most dominant variable number of tourist visits, hotel occupancy rates, length of sray of tourist to the economic growth of South Kalimantan periode 2002-2016. The research data used is secondary data, which is collecting data through the publication of the Central Statistics Agency of South Kalimantan Province. The technique used by this study is descriptive analysis and multiple liner analysis techniques. Bases on the analysis obtained results tha the number of tourist visits, hotel occupancy rates, and length of stay of tourists influences simultaneously on economic growth and the most dominant variabel is the number of tourist visits. While the variable length of stay of tourist is not significant to economic growth. The results of variable testing regression were carried out through SPSS version 20.Keywords: Number of Tourist Visits, Hotel Occupancy Rates, Touris Stay Lengths, Economic Growth.